KOMPONEN MAKNA DALAM KEGIATAN BERLADANG PADI MASYARAKAT DAYAK KANAYATN KABUPATEN LANDAK - Ritno, Ritno; Madeten, Sisilya Saman; Simanjuntak, Hotma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is the words that exist in the activity of ‘paddy farming Dayak Kanayatn Landak District, in Simpang Tiga Village, Village Tapakng, Sompak Subdistrict, Landak District Source of data in this study is the MPA spoken by the informants Dat collection techniques is a technique of simak and skill and fishing techniques Data collection tools of paddy farming in the list of data card questions and recording devices Based on the results of the research analysis shows that the Camponent of Meaning in the Activity of Rice Field (MDKKLO has 33 component vocabulary akna 33,and the tpye of meaning 32 Components of MDKKL meaning that is analyzed with using the analysis of the meaning of the word paddy field, the form of the word paddy field the meaning of rice fields, and the meaning of paddy fields, there are lexical meanings, grammatical meaning of paddy fields, referential eating of nonreferential meaning of rice fields, deotatif meaning connotative meaning of adi and the meaning of the term paddy fields Keywords: Component of Meaning, Rice Field